2010
DOI: 10.1111/j.1532-5415.2009.02631.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Caregiver Health: Findings from the Resources for Enhancing Alzheimer's Caregiver Health II Intervention

Abstract: OBJECTIVES To examine the relationships between changes from baseline to post-Resources for Enhancing Alzheimer's Caregiver Health (REACH) intervention in caregiver (CG) self-reported health, burden, and bother. DESIGN Randomized, multisite clinical trial. SETTING CG and care recipient (CR) homes in five U.S. cities. PARTICIPANTS Four hundred ninety-five dementia CG and CR dyads (169 Hispanic, 160 white, and 166 African American) receiving intervention and their controls. INTERVENTION CGs were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
187
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(197 citation statements)
references
References 44 publications
5
187
0
5
Order By: Relevance
“…This is largely explained by the increased burden generated by the excess of work and responsibilities involved in caring for demented patients, in addition to the emotional implications of having a family member with declining cognitive skills and functional autonomy, in addition to an array of behavioral problems. Therefore, consequences to global health of family caregivers involves physical and psychological symptoms, which in due term may overburden the public healthcare system 1 .…”
Section: Introductionmentioning
confidence: 99%
“…This is largely explained by the increased burden generated by the excess of work and responsibilities involved in caring for demented patients, in addition to the emotional implications of having a family member with declining cognitive skills and functional autonomy, in addition to an array of behavioral problems. Therefore, consequences to global health of family caregivers involves physical and psychological symptoms, which in due term may overburden the public healthcare system 1 .…”
Section: Introductionmentioning
confidence: 99%
“…A multisite trial on Hispanic, Latino and Caucasian caregivers found that the intervention group experienced significant greater improvement in quality of life and lower prevalence of clinical depression than the control group [65]. …”
Section: Family Interventionsmentioning
confidence: 99%
“…Preventing and/or ameliorating caregiver stress is vital to sustaining family caregivers. Evidence based car egiver intervention programs have demonstrated positive results for improving caregiver well-being and reducing stress [16]. However, there is a dearth of interventions that report cultural tailoring [11].…”
Section: Introductionmentioning
confidence: 99%